COPE for Asthma: Outcomes of a Cognitive Behavioral Intervention for Children With Asthma and Anxiety - McGovern, Colleen Marie (Sch Psychol, 2019)
Asthma is the most common childhood chronic condition and a major contributor to school absences and lost instructional time. Children with asthma have a higher risk of internalizing disorders, such as anxiety and depression, which can further complicate asthma management. The purpose of this pilot study was to assess the feasibility, acceptability, and preliminary effects of a manualized, cognitive–behavioral skills-building intervention for children with asthma and anxiety. The design for this study was a one-group, pre/posttest preexperimental with a 6-week follow-up. This article presents the immediate posttest follow-up results. Children between 8 and 12 years of age and their caregivers were recruited from three elementary schools in a large public school district in Ohio. Thirty-two children with asthma and symptoms of anxiety completed the Creating Opportunities for Personal Empowerment (COPE) for Asthma program. Caregivers completed surveys, but they did not participate in the intervention. Results indicated that the program was feasible to implement in small groups during the school day. Self-reported findings indicated a significant reduction in separation anxiety and increased personal beliefs, child-management self-efficacy, and asthma illness representations. Parents and caregivers reported symptom reduction in their children on the Pediatric Symptom Checklist. The subgroup of children scoring high on anxiety at baseline showed reductions with the intervention, having large positive effect sizes for separation and social anxiety as well as medium and large positive effect sizes on the personal beliefs and asthma illness representations, respectively.